UPAYA PEMERINTAH DESA DALAM MENINGKATKAN KESEJAHTERAAN SOSIAL MASYARAKAT - Muten Nuna; Abdul Wahab Podungge; Muh. Fachri Arsjad; Dikson Junus; Nirmala A. Sahi (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research uses a qualitative descriptive method with an analytical method, namely research that produces descriptive data in the form of written or spoken words from people and behavior that can be observed, and uses data collection techniques in three ways, namely observation, direct interviews with specified respondents and documentation. The results of this research show that the village government's efforts to advance the social welfare of the community in North Mongiilo Village, Bulango Ulu District are quite good, even though the level of social welfare of the community in the village itself is not evenly distributed throughout the community, which can be seen from several role indicators. used are: 1) Socialization, where the involvement of the village government together with community leaders in socializing various social welfare development activities for the community in North Mongiilo Village, Bulango Ulu District; 2) Inheritance of knowledge traditions, where the involvement of the village government together with community leaders in providing knowledge to the community regarding the importance of improving the social welfare of the community in North Mongiilo Village, Bulango District; 3) Uniting community groups, where the village government is involved with community leaders in uniting community groups; and 4) Activating the management and control system, where the involvement of the village government together with community leaders in activating the management and control system for development activities in North Mongiilo Village, Bulango Ulu District. The recommendation of this research is that the North Mongiilo Village Government, Bulango Ulu District and community leaders must pay more attention to the level of social welfare of the community and be able to overcome problems regarding the social welfare of the community in the village, such as increasing employment opportunities for the community, increasing scholarship quotas and improving educational facilities in villages, complete health support facilities and infrastructure for the community, continue to socialize various development activities in the village, so that development of the social welfare of the community in the village can be carried out optimally.